Aktivitas Penghambatan Enzim Alfa Glukosidase Oleh Ekstrak Etanol Daun Ubi Jalar Ungu (Ipomoea batatas L.) - Puspitayanti, Inna Ramadhani; , Dr. Muhtadi, M.Si (2017)
Diabetes mellitus was a disease that was the source of the bad health on the world. One of the diabetes mellitus treatment was by inhibiting the enzyme α-glucosidase. Antidiabetic drug had been widely used for therapy, but most antidiabetic and insulin drugs had the larger side effect than traditional drugs. Sweet potato leaves often used as a traditional antidiabetic drugs. This study aimed to determine the activity of α-glucosidase enzyme inhibition by ethanol extract of purple sweet potato leaves, the IC50 value and the kinetisc of the inhibition. The ethanol extract of purple sweet potato leaves was obtained by maceration of powder of plants using 96% ethanol. Inhibition test was divided into reactions with extracts and reaction without extract. Acarbose be a positive control. IC50 results obtained from linear regression of absorbance vs concentration of the extract. Kinetics test was using the inhibitor reaction and without inhibitor. The consentration extract used to kinetics test is the concentration that could inhibit the enzyme by 50% . Absorbance of the both test was read at wavelength 400 nm using ELISA reader. The study results obtained that ethanol extract of purple sweet potato leaves could inhibit enzyme activity α-glucosidase with an average IC50 value 22,39μg / mL. Result of kinetic test obtained that this inhibition sample type belongs to mixed-type inhibiton.